From Personhood to Panim: God's Immortal Image according to Father Stăniloae - Tănase, Nichifor (Diakrisis, 2025)
According to Father Stăniloae, if God is transcendent, He is persona, and His personal character assures His transcendence. His persona transcends even His infinity. Likewise, the image of God in man lies essentially in the character of the person: every person becomes a new "eye" of spiritual transparency. The most adequate, expressive and communicative image of the supreme Image is the human being, or more precisely, the human face. Starting from the fact that personhood is no longer experienced as a mystery, Stăniloae turns to the Bible, which testifies that the face (panim) is the essence of a person. This biblical theology of God's shining face or presence (panim) is the key to understanding Father Stăniloae’s eschatology and, by extension, his entire theology of the person. There is a dynamic and revelatory movement from the anthropological dimension of eikon-tselem ("image of God") in his earlier studies, such as God's Immortal Image, to the later theology of personhood in Volume 6 of his Dogmatics, which is indebted to the biblical dimension of prosōpon-panim (the human "face" of Christ). Eternal bliss, according to him, will be the contemplation of the face of Christ; this is the "eternal perspective of deification" - the divine energies conceived in and radiated from the face of Christ.